Gendered Bricks: A Semiotic Approach to the Marketing of Lego in Singapore - Rodriguez, Maxine Rafaella C.; Go, Christian (Journal of English Studies and Comparative Literature; Vol 18 No 2 (2019), 2019)
Toys perpetuate dichotomization of gender, as evidenced by a multimodal analysis of Lego marketing. Employing multimodal critical discourse analysis and geosemiotics as frameworks, this study answers the research question:“How does Lego (re)produce gendered discourses vis-à-vis toy marketing in Singapore?” While Lego does not present sufficient textual evidence of marketing their products as either and exclusively for girls or boys, semiotic resources of color, space, product design, type fonts, and suggested activities for play on toy packaging, on the website, and in Bricks World Singapore, collectively index which gender the manufacturer positions as its target consumer. Lego is primarily targeted at boys, indexed as “default,” while those targeted at girls are “marked variants,” propagating gender segregation and asymmetry among young and impressionable toy consumers. The study recommends the consumption of gender-neutral toys to lessen chances of gendering childhood socialization and play, bullying, and gender policing especially among children.